Lifestyle Change Interventions for Children and Adolescents With Diabetes or Kidney Disease - Lori L. Sanderson MSW, MPH (SAGE Publishing, 2010)
The purpose of this research letter is to report on the availability of evidence-based interventions for promoting lifestyle change in children and adolescents with diabetes or kidney disease. References for this review were obtained using several electronic databases, including Ebsco Host, PsychInfo, Medline, and CINAHL. Search topics included transplant adherence, diabetes adherence, kidney adherence, obesity and transplant, kidney disease, transplant noncompliance, renal failure, renal disease, chronic kidney failure, end-stage renal disease, obesity and diabetes, overweight and kidney disease, overweight and diabetes, overweight, treatment interventions and overweight, treatment interventions for obesity, children and obesity, growth chart, diabetes intervention, kidney disease intervention, obesity intervention, obesity and transplantation, obesity transplant intervention, motivational interviewing, physical activity level, physical activity, exercise intervention, body mass index measurement, body fat percentage, psychosocial issues of kidney disease, psychosocial issues of transplant, and coping with kidney disease. Search results included English language only and between the years 2000 and 2009. Very few lifestyle interventions have been shown to be effective for obese children or adolescents with diabetes and none for obese children and adolescents with kidney diseases. More research is needed to develop effective interventions for this vulnerable population.